Dynamic Changes in Liver Function Tests and Their Correlation with Illness Severity and Mortality in Patients with COVID-19: A Retrospective Cohort Study - Xu W; Huang C; Fei L; Li Q; Chen L (Clinical Interventions in Aging, 2021)
Wei Xu,* Chenlu Huang,* Ling Fei,* Qiang Li, Liang Chen Department of Liver Diseases, Shanghai Public Health Clinical Center, Fudan University, Shanghai, 201508, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiang Li; Liang Chen Email liqiang66601@163.com; chenliang@shphc.org.cnObjective: To describe the longitudinal changes in liver function tests, and their association with illness severity and mortality in patients with COVID-19.Methods: A retrospective cohort study of 1003 hospitalized patients with COVID-19 was conducted. Longitudinal liver function tests and clinical outcomes were analyzed.Results: Abnormal liver function parameters were observed, both at admission (ALT 13.2%, AST 8.5%, ALP 2.0%, GGT 7.4%, LDH 37.6%, TBIL 4.0%, DBIL 7.8%, Albumin 10.1%) and peak hospitalization (ALT 29.4%, AST 17.5%, ALP 2.6%, GGT 13.4%, LDH 49.4%, TBIL 10.1%, DBIL 18.0%, Albumin 30.6%) in patients with COVID-19. Compared with non-severe patients, severe patients had markedly higher liver function parameters from baseline to 30 days after hospital admission. Abnormal ALT and LDH at hospital admission and some medications use (Hydroxychloroquine, Lopinavir/Ritonavir, and Traditional Chinese medicines) were associated with peak hospitalization ALT > 5× the upper limit unit of normal (ULN). On multivariate analysis, age > 60 years, male, obesity, comorbidity, abnormal LDH and albumin at hospital admission and peak hospitalization were associated with progression to severe COVID-19 (OR > 1; p < 0.05). COX analysis revealed that ALT > 2 ULN (HR=7.0, p=0.011), AST > 2 ULN (HR=34.7, p < 0.001), and TBIL > 2 ULN (HR=54.6, p < 0.001) were associated with a higher mortality.Conclusion: Dynamic abnormalities of liver function parameters are common in hospitalized patients with COVID-19, and associated with illness severity and mortality.Keywords: COVID-19, SARS-CoV-2, liver function parameters, liver injury, clinical outcomes